High-fat Feeding Causes Inflammation and Insulin Resistance in the Ventral Tegmental Area in Mice. (1st May 2021) - Mizoguchi, Akira; Banno, Ryoichi; Sun, Runan; Yaginuma, Hiroshi; Taki, Keigo; Kobayashi, Tomoko; Sugiyama, Mariko; Tsunekawa, Taku; Onoue, Takeshi; Takagi, Hiroshi; Hagiwara, Daisuke; Ito, Yoshihiro; et al.
Graphical abstract: Highlights: A high-fat diet (HFD) causes inflammation with microglial activation in the ventral tegmental area (VTA). A HFD induces insulin resistance in the VTA at a relatively early stage, independent of the energy balance. Our data shine light on the pathophysiology of obesity caused by a dysfunctional reward system related to high fat intake. Abstract: The reward system plays an important role in the pathogenesis of not only drug addiction, but also diet-induced obesity. Recent studies have shown that insulin and leptin receptor signaling in the ventral tegmental area (VTA) regulate energy homeostasis and that their dysregulation is responsible for obesity and altered food preferences. Although a high-fat diet (HFD) induces inflammation that leads to insulin and leptin resistance in the brain, it remains unclear whether HFD induces inflammation in the VTA. In the present study, we placed male mice on a chow diet or HFD for 3, 7, and 28 days and evaluated the mRNA expression of inflammatory cytokines and microglial activation markers in the VTA. The HFD group showed significantly elevated mRNA expressions of IL1β at 3 days; tumor necrosis factor-alpha (TNFα), IL1β, IL6, Iba1, and CD11b at 7 days; and TNFα, IL1β, Iba1, and CD11b at 28 days. The changes in TNFα were also confirmed in immunohistochemical analysis. Next, after administration of chow or HFD for 7 days, we selected mice with equal weights in both groups. In experiments using these mice, Akt phosphorylation in the VTA was significantly decreased after intracerebroventricular injection of insulin, whereas no change in STAT3 phosphorylation was found with leptin. Taken together, these results suggest that HFD induces inflammation at least partly associated with microglial activation in the VTA leading to insulin resistance, independently of the energy balance. Our data provide new insight into the pathophysiology of obesity caused by a dysfunctional reward system under HFD conditions.